Comparative Analysis of Spirulina and Chlorella: Extraction, Drying Technologies and Applications in Agriculture - Salimova, I. Y.; Salimova, N. Y. (American Journal of Biodiversity, 2025)
Microalgae are unique sources of biologically active substances that are in demand in the food, pharmaceutical and agricultural industries.The most studied representatives are Arthrospira platensis (spirulina) and Chlorella vulgaris (chlorella), which are characterized by a high content of proteins, vitamins, minerals and pigments. The aim of this work is to systematize current data on microalgae extraction and drying methods, as well as to analyze their application in agriculture. Alkaline and enzymatic extraction, as well as mechanical methods of destruction of cellular structures, are considered. Approaches to drying (freeze-drying, spray-drying, heat-drying) are generalized and their influence on the preservation of biological activity of biomass is shown. Special attention is paid to animal feed additives, биостимуляцииplant biostimulation, and the ecological potential of algae. It is concluded that there are high prospects for the use of microalgae in the agro-industrial complex and the need for further optimization of technologies.